Socio- Demographic Study of Deaths Due to Poisoning in Autopsies Conducted at KIMS Hospital, Bangalore - Senthil Kumar V1, A. Dominic Infant Raj2, Naveen Kumar.T3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Poisoning is a common day to day problem. Profile of poisoning in an area depends upon a variety of factors, ranging from access to and availability of poison, socio-economic status of the individual, cultural and religious influences, etc. A prospective study was carried out in the Department of Forensic medicine, Kempegowda Institute of Medical Sciences and Hospital Bangalore to study the socio- demographic profiling of deaths due to poisoning. Out of the 100 cases studied, incidence of poisoning was found to be more amongst the age group of 21 to 30 years in both sexes with mean age being 25.4 years and 25.4 years amongst males and females respectively. Poisoning is more in males (68%) as compared to females. In both the sexes, married (68%) outnumbered the unmarried in rural and urban community. This study shows that maximum number of poisoning cases were noticed among Upper Lower socio economic Class and in Nuclear families(61%). It was observed that majority of the victims were Graduate (28%).Financial constraints(22%) were the most common motive behind poisoning deaths.